The burden of vitamin D deficiency in household members of children presenting with symptomatic vitamin D deficiency - Uday, Suma; Högler, Wolfgang (Frontiers in Endocrinology, 2022)
Background: Micronutrient deficiencies are common among household/family members due to shared lifestyle and dietary habits. The extent of biochemical abnormalities in household members of children presenting with symptomatic vitamin D deficiency remains unknown. Aims: Investigate the prevalence of vitamin D deficiency and biochemical osteomalacia in the mothers and siblings of children presenting with symptomatic vitamin D deficiency. Methods: All mothers and sibling of children referred to a single tertiary endocrine centre between January 2018 and December 2021, with symptomatic vitamin D deficiency were investigated prospectively for vitamin D deficiency [defined as 25 hydroxyvitamin D (25OHD) < 30nmol/L] and biochemical osteomalacia [vitamin D deficiency and elevated alkaline phosphatase (ALP) and/or parathormone (PTH)] as per clinical guidelines. Results: Ninety-seven family members (68 siblings and 29 mothers) of 29 index cases (median age 1.7 years, 55.5% male) were investigated. The majority (65.5%, n=19) were of Asian ethnic background. The mean (SD) 25OHD levels of the index, maternal and sibling cohorts were 15 (10), 15 (7) and 20 (10) nmol/L respectively. Vitamin D deficiency was noted in 93% of the maternal and 79% of the sibling cohorts. Biochemical osteomalacia was present in 72% of the maternal and 79% of the sibling cohorts. Mothers of infants had significantly lower mean 25OHD levels compared to mothers of older children [11 (n=12) vs 18 nmol/L (n=17) respectively, p=0.006)], most of whom were symptomatic (66.6%, n=8/12). None of the mothers had hypocalcaemia. Among the 10% (n=7) of the siblings with hypocalcaemia, 86% (n=6/7) had concurrent dietary calcium deficiency and 71.4% (n= 5/7) reported symptoms in retrospect. Hypocalcaemic siblings had significantly lower 25OHD (7 vs 15 nmol/L, p<0.001), higher PTH (175 vs 58 ng/L, p<0.001) and ALP (846 vs 318 IU/L, p<0.001), respectively compared to normocalcaemic siblings. Conclusions: In view of the substantial morbidity uncovered in household/family members of children diagnosed with symptomatic vitamin D deficiency, we recommend universal supplementation of all risk groups. Biochemical testing and treatment is indicated to replenish stores only in those at highest risk such as mothers of infants, individuals with concurrent dietary calcium deficiency and those with clinical symptoms.